AlloHSCT for inv(3)(q21;q26)/t(3;3)(q21;q26) AML: a report from the acute leukemia working party of the European society for blood and marrow transplantation. (June 2018) - Halaburda, Kazimierz; Labopin, Myriam; Houhou, Mohamed; Niederwieser, Dietger; Finke, Jürgen; Volin, Liisa; Maertens, Johan; Cornelissen, Jan; Milpied, Noel; Stuhler, Gernot; Kröger, Nicolaus; Esteve, Jordi; et al.
Abstract Acute myeloid leukemia with inv(3)(q21;q26.2)/t (3;3)(q21;q26.2) (3q26 AML) is a rare disease with poor prognosis and median survival of <1 year. To evaluate allogeneic stem cell transplantation (alloHSCT) in the treatment of 3q26 AML, we studied 98 patients reported to the European Society for Blood and Marrow Transplantation between 1995 and 2013. Majority of patients were transplanted using peripheral blood, from unrelated donors and after myeloablative conditioning. Fifty-three patients were transplanted with active disease and 45 in complete remission. After a median follow-up of 47 months, 2 year leukemia-free survival (LFS), overall survival (OS), relapse incidence (RI), non-relapse mortality (NRM), and graft-versus-host disease-free, relapse-free survival (GRFS) probabilities were 20%, 26%, 64%, 16%, and 14%, respectively. Two-year LFS and OS probabilities for patients transplanted in CR vs. those transplanted in active disease were 23.8 vs. 17% (p  = NS) and 34.9 vs. 18.9% (p  = NS), respectively. In multivariate analysis CR was the only factor associated with a trend for better LFS (p  = 0.05, HR 0.64) and OS (p  = 0.06, HR 0.65). CR also significantly influenced GRFS (p  = 0.01; HR 0.55) and NRM (p  = 0.02; HR 0.27). The results suggest that a proportion of patients might benefit from the procedure, especially if performed in CR.